DIURETICS EFFECT OF SALAK (Salacca zalacca) SEED EXTRACT TO KIDNEY HISTOPATHOLOGICAL STRUCTURE OF THE WISTAR MALE RATS (Rattus norvegicus) - Rike Oktarianti; Nur Aisyah Septiana; Asmoro Lelono (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
Salak seed are used as natural diuretics, it's contain secondary metabolites i.e alkaloids, flavonoids and tannins. Diuretics are compounds that can increase the rate of excretion of urine volume and increase the excretion of mineral salts in the urine. The study was to determine the diuretic effect of salak seed extract on the histopathological structure of the kidney. Salak seed extract was made by maceration method using 70% ethanol and then evaporated. Rats were divided into 4 treatment groups, negative control and 3 treatment groups with the administration of salak seed extract for 7 days orally at a dose of 0.28g/kg body weight, 0.56g/kg body weight and 1.12g/kg body weight. The results showed that the treatment of salak seed extract orally for 7 days could increase urine volume. The treatment of dose 1.12g/kg body weight had highest diuretic effect as indicated by the volume of urine produced 5.00 ml. The treatment salak seed extract had no effect on creatinine and urea levels. The all treatment doses of salak seed extract had no effect on the kidney histopathological structure, i.e it was not effect on glomerular diameter or did not cause atrophy of kidney glomerular.